The Role of Local Culture in the Formation of Marketing Communication Networks for Microenterprise Sustainability in Coastal Areas - Subekti, Priyo; Sjuchro, Dian Wardiana (Komunikasiana: Journal of Communication Studies, 2024)
This research aims to examine the importance of marketing communication networks in the growth of micro-enterprises and appreciate the role of social and technological integration in developing culture-oriented marketing networks. The case study method was employed with a descriptive qualitative research design. The data was collected through in-depth interviews, participatory observation, and analysis of documents related to marketing strategies. A purposive sampling technique was adopted in sampling micro-entrepreneurs engaged in trade and tourism within the coastal region of Pangandaran Beach. The study depicts local values such as togetherness, gotong royong, and trust networks as values-based marketing communication that bridges the micro-enterprises and the local communities, families, and business partners. Social media proved otherwise in extending the marketing network through technological adaptation and brand recall. In addition, engagement with government institutions and other similar sectors, such as distributors and tourism actors, also contributes significance to the stability of the microenterprise. In summary, the inclusion of local cultural elements into marketing communicational networks creates a synergy that enhances not only the marketing strategies but also the viability of the micro-enterprises operating in the coastal region. This study helps policymakers and businesses devise culture-centered marketing strategies to enhance the growth of the local economy.